Determination of Chlorzoxazone Crystal Growth Kinetics and Size Distribution under Controlled Supersaturation at 293.15 K - Satish G (Tabriz University of Medical Sciences, 2021)
Background: Chlorzoxazone (CHZ) is a water-insoluble drug having bioavailability problems. The absorption rate of such drugs can be improved by reducing their particle size. In this work, the crystal growth kinetics of CHZ–ethanol for different degrees of supersaturation (SS) has been studied. Methods: The equilibrium solubility data of CHZ in ethanol is determined by the shake-flask method within the 283.15–313.15 K temperature range. The mole fraction solubility of CHZ is calculated and correlated with the modified Apelblat equation, λh equation, van’t Hoff equation, Wilson, and non-random two liquid (NRTL) equation. Batch crystallization experiments are performed on three different degrees of SS-1.16, 1.18, and 1.20 at 293.15 K as a function of time. Results: The maximum root mean square difference (RMSD) and relative average deviation(RAD) values of 169.24 x10-6 and 0.699 x10-2, respectively, are observed in the NRTL equation model. The dissolution properties such as standard enthalpy, standard entropy, and Gibbs free energy are predicted using van’t Hoff equation. Using a simple integral technique, the average crystal growth rate constant KG is calculated as 1.58 (μm/min) (mg/ml)-1 and the order n=1 for CHZ–ethanol at 293.15 K. Conclusion: The obtained result concludes that the crystal’s growth size is found to be varied at different SS ratio in batch crystallization. The particle size control in batch crystallization can be achieved by optimizing the operating conditions to get the desired size crystals.